Perancangan Dan Realisasi Sistem Harvesting Dan Distribusi Catu Daya Pada Satelit Kubus - Rahman, Saifur; Edwar; Ramdhani, Mohamad (eProceedings of Engineering, 2024)
Cube satellites are typically used as platforms for experiments and observation. Therefore, a reliable electrical distribution system is needed to ensure the cube satellite can operate stably and optimally. In this research, a prototype system was designed and implemented based on needs analysis and specifications. The developed system has functions such as the ability to control power harvesting conditions, electrical distribution, as well as monitoring the voltage on solar panels and batteries. Thanks to the testing conducted, it was proven that this system works correctly and can be an effective solution to improve the performance of cube satellites in future research. Keywords: electrical power system, satellite electrical distribution